2022
DOI: 10.3390/agriculture12101694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Dietary Condensed Tannins from Sainfoin (Onobrychis viciifolia) on Gut Health and Antioxidant-Immune Crosstalk in Suckling Lambs

Abstract: Ewes fed sainfoin (a source of condensed tannins “CT”) may influence the homeostasis of the gastrointestinal tract of suckling lambs. This study investigated the effects of CT from sainfoin in the maternal diet on plasma fructosamine, faecal coccidian excretion, and gene expression of immune and antioxidant markers in jejunum and ileum of suckling lambs. Twelve Rasa Aragonesa lambs with their dams were selected. The maternal diet was based on fresh sainfoin (SAINFOIN, n = 6) and sainfoin + polyethylene-glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…The results showed that a P. granatum -based remedy reduced GIN egg output by 50%. Furthermore, according to Pelegrin-Valls et al ( 2022 ), feeding suckling lambs sainfoin has a positive effect on reducing coccidian oocysts. Phytobiotic additives, particularly those with high polyphenol content (e.g., tannins and flavonoids), triterpenoids, and saponin, have anthelmintic effects by forming complexes with protein in the rumen and increasing amino acid absorption by the small intestine (Tchetan et al 2022 ), which improves host homeostasis and immunomodulatory of the host against various parasites (Min et al 2003 ).…”
Section: Effects Of Phytobiotic Additives On Animal Healthmentioning
confidence: 99%
“…The results showed that a P. granatum -based remedy reduced GIN egg output by 50%. Furthermore, according to Pelegrin-Valls et al ( 2022 ), feeding suckling lambs sainfoin has a positive effect on reducing coccidian oocysts. Phytobiotic additives, particularly those with high polyphenol content (e.g., tannins and flavonoids), triterpenoids, and saponin, have anthelmintic effects by forming complexes with protein in the rumen and increasing amino acid absorption by the small intestine (Tchetan et al 2022 ), which improves host homeostasis and immunomodulatory of the host against various parasites (Min et al 2003 ).…”
Section: Effects Of Phytobiotic Additives On Animal Healthmentioning
confidence: 99%